HUBUNGAN DUKUNGAN SUAMI DENGAN PRAKTIK PEMBERIAN ASI EKSKLUSIF PADA IBU PRIMIPARA (Studi di Wilayah Kerja Puskesmas Jebed Kabupaten Pemalang) - Tias Larasati; Dina Rahayuning Pangestuti; M. Zen Rahfiludin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Exclusive Breastfeedingsince the first six months is an effort to produce the next healthy generation, quality as well as obtaining good growth. New mothers first baby (primipara) will experience a variety of problems with breastfeeding, such as how to put the baby on the breast, the milk does not come out and other problems that could thwart his mother in breastfeeding,thus need support for breastfeeding practice. Out of all the supports, the support of the husband is most significant support for mothers. The purpose of this research was to analyze the relationship between husband support to exclusive breastfeeding practice in primipara mothers in Puskesmas Jebed Pemalang. This research is explanatory research with designs cross sectional. The sample in this study were married couples for the first time had children aged 0-6 months with the amount of 46 couples. The sampling technique used method proporsional random sampling. Data analysis used Chi Square. The results showed the practice of exclusive breastfeeding in primipara mothers amounting to 34,8%. Statistical analysis showed the support of husband significantly related to the practice of exclusive breastfeeding in primipara mothers including emotional support (p=0,001), informational support (p=0,001), support asessment (p=0,001), instrumental support (p=0,007). The practice of exclusive breastfeeding also influenced by other factors such as family support (p=0,005), and parenting (p=0,016) which is also associated significantly. It can be concluded that the husband able to play an active role in supporting mothers practice exclusive breastfeeding, husband supports is one of the important factors in increasing the success of the practice of exclusive breastfeeding.